Political theory of global justice : a cosmopolitan case for the world state - Cabrera, Luis, 1966- (Routledge innovations in political theory, 2004)
This book offers a moral argument for world government, claiming that not only do we have strong obligations to people elsewhere, but that accountable integration among nation-states will help ensure all persons can lead a decent life.